2008
DOI: 10.1007/s00330-008-0955-4
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of ultrasound-guided, large-core needle breast biopsy

Abstract: Ultrasound-guided, large-core needle biopsy (US-LCNB) of suspicious breast lesions is acknowledged as less invasive and less expensive and less time consuming than surgical biopsy, and provides a histologic diagnosis with a comparable high degree. US-LCNB has been proven to help reduce the number of unnecessary surgeries for benign disease. Its limitations, however, are false-negative results and underestimation of disease. Thus, the demand for breast teams is to carefully adhere to the principles of triple as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
1
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 88 publications
(55 reference statements)
4
59
1
10
Order By: Relevance
“…If the result is malignant then therapeutic procedures may be directly applied. The rate of detecting malignancy after surgical excision of BI-RADS 4-5 lesions varies between 15-40%, while this rate varies between 70-80% in surgical excision after detection of malignancy by radiologic sampling methods (12,13). Meta-analyses including many studies state that radiologic biopsy methods should be preferred to surgical biopsy, if it can be performed (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…If the result is malignant then therapeutic procedures may be directly applied. The rate of detecting malignancy after surgical excision of BI-RADS 4-5 lesions varies between 15-40%, while this rate varies between 70-80% in surgical excision after detection of malignancy by radiologic sampling methods (12,13). Meta-analyses including many studies state that radiologic biopsy methods should be preferred to surgical biopsy, if it can be performed (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasoundguided core needle biopsy is considered to be a reliable non-invasive alternative to surgical biopsy for obtaining a histopathological diagnosis with considerable sensitivity and specificity. However, its limitations include relatively high false-negative results (range 0.9-9.0%) and underestimation of disease with a wide range (17), suggesting that it is necessary to perform intraoperative assessment for patients with DCIS diagnosed by core needle biopsy who may need SLNB. Studies have indicated that lobular histology may be more difficult to interpret using touch imprint cytology, leading to a higher false-negative rate (18).…”
Section: Discussionmentioning
confidence: 99%
“…Görüntüleme bulguları değerlendirilerek yapılan örneklemelerde malignite tespit oranı %20 düzeylerindedir. BI-RADS 4-5 lezyonda malignite teşhis oranları direk eksizyon yapı-lan örneklemelerde %15-40 arasında değişir-ken, görüntüleme eşliğinde yapılan biyopsiler sonrasında %70-80 arasındadır [3,4]. Görün- tüleme eşliğinde biyopside hedef, konservatif tanı oranını en üst düzeye çıkarmak ve tekrar iğne biyopsi prosedürleri sayısını en aza indirmek için hatalı örnekleme sayısını %5'in altına düşürmektir [4].…”
unclassified